Biogenic Amines and Aflatoxins in Some Imported Meat Products: Incidence, Occurrence, and Public Health Impacts - Fahad Dhafer Algahtani; Alaa Eldin Morshdy; Mohamed A. Hussein; Essam Said Abouelkheir; Adeniyi Adeboye; Andrea Valentine; Mohamed Tharwat Elabbasy (Journal of Food Quality, 2020)
Background. Since the beginning of humanity, the global burden of foodborne disease has had a decimating effect on populations, with biogenic amines (BAs) and aflatoxins in meat products implicated. While many developed countries have legitimized safety levels for BAs using evidence-based guidelines to attain high food quality standards for consumers of meat products, developing countries are still battling against poor food quality checking. Purpose. This study examines the level of health risk of biogenic amines and aflatoxin in meat products by extracting and estimating their residues and determining their indices as a way of monitoring the potential health impacts of these residues on consumers of meat products. Methods. A total of 40 imported meat products sampled and randomly collected, representing imported luncheon meat, hot dog sausages, corned beef, and minced meat. Using recommended laboratory protocols, eight residues of BAs and aflatoxins were extracted. Results. Eight BAs, histamine, tyramine, tryptamine, cadaverine, putrescine, β-phenyl ethylamine, spermine, and spermidine, were extracted and determined in all tested samples. Tyramine levels in luncheon meat were found to be significantly higher than in other meat products, while significantly high cadaverine levels were reported in corned beef samples. The results of biogenic amine index (BAI) revealed that the quality of imported minced meat and imported hot dog samples was good (BAI < 5 mg/kg), while imported luncheon meat and imported corned beef samples remained acceptable (BAI 5–20 mg/kg). Aflatoxin B1 (AFB1) was detected higher than the permissible limit (>5 µg/kg) in imported luncheon meat and imported hot dog meat samples. Conclusion. The general results indicate that testing meat products for biogenic amines and aflatoxins is a very good indicator for monitoring the freshness and quality of meat products.